Syntax Score I and II for Predicting Carotid Artery Stenosis in Patients with Multivessel Coronary Artery Disease: A Propensity Score Matching Analysis - Ozturk,Semi (2019)
Abstract Objective: To evaluate the predictive accuracy of SYNTAX score (SS) I and II for detecting significant carotid artery stenosis (CAS) in patients with multivessel coronary artery disease undergoing coronary artery bypass grafting (CABG) surgery. Methods: The study population consisted of 416 patients. Clinical, demographic, and radiological records were retrospectively reviewed. Characteristics of patients with CAS (n=66) and patients without CAS (n=350) were compared before and after propensity score matching analysis. Results: Patients with significant CAS were older compared to those without significant CAS [(60 (53-65) vs. 63 (59-67); P=0.01]. However, atherosclerotic risk factors and SS I were similar between groups. SS II CABG and percutaneous coronary intervention (PCI) were significantly higher in patients with CAS [37.4 (30.9-43.5) vs. 33.8 (29.9-38.9); P=0.02]. After propensity score matching analysis (66 vs. 66), age, SS II PCI and CABG were significantly higher in patients with CAS than those without CAS [37.4 (30.9-43.5) vs. 33 (29.3-36.9); P=0.03]. Age, SS II PCI and CABG were associated with CAS in logistic regression analysis [OR=1.086, 95% CI (1.032-1.143), P<0.001; OR=1.054, 95% CI (1.010-1.101), P=0.02; OR=1.078, 95% CI (1.029-1.129), P<0.01]. In ROC curve analysis, SS II PCI >33.1 had 68.2% sensitivity and 54.6% specificity [AUC=0.624, P=0.01, 95% CI (0.536-0.707)] whereas SS II CABG >26.1 had 81.8% sensitivity and 54.6% specificity [AUC=0.670, P<0.01, 95% CI (0.583-0.749)] to predict CAS. Pairwise comparison of ROC curves revealed similar statistical accuracy for prediction of CAS (z statistic: 0.683, P=0.49) Conclusion: SS II is useful to predict asymptomatic CAS in patients with multivessel coronary artery disease.